Rational faith as moral belief and the objection of atheism in What is orientation in thinking? - Beade, Ileana Paola (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In several writings, Kant argues that, both in the realm of the theoretical use of reason and in its practical use, this faculty is the origin of a priori representations, which determine both knowledge of objects and action - understood in a practical or moral sense-. In a 1786 text, What is orientation in thinking?, he argues that reason is authorized to suppose something that it is radically incapable of knowing, namely the existence of a supreme being, and that the representation of an existing God is an inescapable result to which reason leads in the exercise of its autonomous capacity. In this context, atheism is considered as a form of dogmatism, that is, as a position that reflects an uncritical and deficient use of reason, and that expresses, ultimately, an incapacity of that faculty to meet the demands that it imposes on itself. The purpose of this paper is to examine the arguments presented in this text in order to deepen the meaning of the Kantian conception of religious faith and rational belief.